240VAC TO ll0VAC VOLTAGE CONVERTER - ALIAS, IRMAN BAKTI (Universiti Teknologi Petronas, 2005)
The main task of this final year project is to design a household 240VAC to 110VAC voltage converter. This converter should be able to supply up to 400 Watts of power, enough to power up a normal household appliances such as vacuum cleaner. A voltage regulator must be included in the design to ensure the protection of any household appliances that uses this converter. This is important to ensure user safety when operating this converter and to protect the equipments that use this converter. The idea of designing this particular converter is by combining an AC-to-DC converter with a DC-to-AC inverter. Thus, the design must be reliable and efficient in term of power conversion. The cost of the design should be minimized since this type of converter is available in the market but the price is quite expensive. The main concern in this design is to minimize the cost needed to build this converter while maintaining its performance.